2011
DOI: 10.1111/j.1399-5448.2011.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Contraception, and pregnancy in adolescents with type 1 diabetes: a review

Abstract: Adolescence is a critical period for girls with type 1 diabetes mellitus (T1D). Reproductive issues, such as menstrual abnormalities, risk of an unplanned pregnancy, and contraception, should be addressed during this phase of life. This paper reviews several reproductive issues that are important in the care of adolescents, including pubertal development, menstrual abnormalities, ovulatory function, reproductive problems, the effects of hyperglycemia, contraception, and treatment of an unplanned pregnancy. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 162 publications
(234 reference statements)
1
44
0
3
Order By: Relevance
“…However, comparison between patients with pre-menarcheal diabetes and a Finnish background population showed that these patients still had a slightly delayed menarche. In Finnish women without diabetes, the mean age at menarche has decreased from 14.9 years in the early 1900s to 12.7 years in the 1970s or later [31], as also seen worldwide [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, comparison between patients with pre-menarcheal diabetes and a Finnish background population showed that these patients still had a slightly delayed menarche. In Finnish women without diabetes, the mean age at menarche has decreased from 14.9 years in the early 1900s to 12.7 years in the 1970s or later [31], as also seen worldwide [25].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some studies show no association between the age at menarche and diabetes [23,24], suggesting that there is still no clear understanding of whether or not the presence of diabetes affects the onset of menstruation and whether this relationship might be dependent on the age at onset of type 1 diabetes. Interestingly, over the years, the age of menarche has progressively been declining and this secular trend has also been observed in girls both with and without type 1 diabetes throughout the world [25].…”
Section: Introductionmentioning
confidence: 99%
“…The diabetes care team should be sensitive to the religious and cultural influences affecting an individual's choice of contraceptive method When a female with diabetes becomes sexually active she should do so with knowledge of how to avoid an unplanned pregnancy and STIs. …”
Section: Sexual Healthmentioning
confidence: 99%
“…Advice to young people with regards to sexual health will vary between different countries and cultures but would usually include : A non‐judgmental approach to sexual activity. Advice where applicable on methods of avoiding pregnancy and sexually transmitted infections (STIs) for male as well as female adolescents. Prevention of hypoglycemia during or after intercourse. Advice on genital hygiene, vulvovaginal candidiasis, menstrual disorders, and STIs. Pre‐pregnancy counseling …”
Section: Sexual Healthmentioning
confidence: 99%
“…The diabetes care team should be sensitive to the religious and cultural influences affecting an individual's choice of contraceptive method . When a female with diabetes becomes sexually active she should do so with knowledge of how to avoid an unplanned pregnancy and STIs ( E ) . …”
Section: Sexual Healthmentioning
confidence: 99%